Comparative analysis of surgical treatment modalities for a popliteal pterygium: a meta-analysis - Aman, Martin; Sidiq, Maiwand; Pennekamp, Anna; Harhaus-Wähner, Leila; Thielen, Mirjam (Archives of orthopaedic and trauma surgery, 2024)
Popliteal pterygium syndrome is a rare congenital disorder characterized by orofacial, cutaneous, musculoskeletal, and genital anomalies. The popliteal pterygium (PP) affects ambulation due to severe knee flexion contracture and equinovarus deformities. Surgical treatment aims to correct these deformities while preserving limb sensibility. However, due to its rarity, surgical guidelines are lacking.
Publikationsdatum: 13. April 2024 (online)
Gesehen am 16.07.2024